Microstructure and ablation properties of La2O3 modified C/C-SiC composites prepared via precursor infiltration pyrolysis. Issue 4 (April 2019) - Fang, Cunqian; Yang, Xin; He, Kejian; Chen, Lei; Zeng, Guang; Shi, Anhong; Huang, Qizhong; Huang, Boyun
Abstract: Effects of La2 O3 modification on the microstructure, mechanical and ablation properties of C/C-SiC composites were investigated. Experimental results show that a new La10 (SiO4 )6 O3 phase was generated during heat treatment process. The presence of the La-compounds, namely La2 O3 and La10 (SiO4 )6 O3, had an important impact on the structure of reinforced skeleton and the molten oxide film, and thus strongly affected the mechanical and ablation properties of the composites. Excessive La addition induced the structural damage of the reinforced skeleton, resulting in weakened mechanical and ablation properties. The C/C-SiC composites with 25.65 wt.% La2 O3 addition displayed better mechanical properties and the best ablation resistance. The La10 (SiO4 )6 O3 phase could react with molten silica to form a viscous glass during ablation. The transformation of La-compounds into La2 Si2 O7 can reduce the ablation of SiO2 and enhance the glass film, so as to protect the composites from further ablation.